Biomarkers of neurodegeneration - Zetterberg, Henrik (Henry Stewart Talks, 2014)
Basic concepts: fluid biomarkers for neurodegenerative diseases, Cerebrospinal fluid biomarkers for Alzheimer's, Parkinson's and other neurodegenerative diseases, Cerebrospinal fluid biomarkers in traumatic brain injury, Peripheral blood biomarkers for brain damage
Archived at 2022/10/02